External Actors in Nigeria’s Solar Energy Transition: A Comparative Analysis of Multinational Corporations, International Organizations, and State-Led Investors - Wang, Shuai (International Journal of Energy Economics and Policy, 2025)
The shift to renewable energy development in fossil fuel-rich developing countries such as Nigeria, is usually influenced by complex interaction among external actors, regulatory frameworks, and entrenched fossil fuel interests. However, how the effectiveness of different types of external actors - international organizations, multinational corporations, and state-led investors – differs, remains unknown. The Nigeria Electrification Project, Ashama Solar Power Plant, and Kaduna Solar Power Project are selected for comparative case study analysis. Using the Multi-Level Perspective framework, the study examines how niche innovations, socio-technical regime, and landscape pressures affect solar energy transition in Nigeria. The findings demonstrate that international organizations-led solar projects have facilitated decentralized electrification but faced with financial sustainability issues; multinational corporations-led projects have driven large-scale installation yet encountered regulatory and market risks; by contrast, state-led projects have exhibited superior stability benefiting from strong government backing and state investor’s geopolitical alignments. Nonetheless, there are also challenges that impede Nigeria’s long-term renewable energy development, such as inconsistent policies, fossil fuel subsidies, and macroeconomic volatility. Therefore, this study highlights the need for a hybrid investment approach that integrates the advantages of each type of external actors while tackling structural barriers. This study provides broader insights to similar fossil fuel-rich developing economies.